Sales Territory Design: An Integrated Approach - Shanker, Roy J.; Turner, Ronald E.; Zoltners, Andris A. (Management Science, 1975)
A sales territory design procedure should solve the dual problems of boundary definition and call frequency. Furthermore, it should be possible to base the design on several workload and potential criteria. A procedure is presented which meets this specification. It employs recent developments in set-partitioning and includes a computer code which makes it possible to handle design problems of realistic proportions. The outcome of the design procedure, termed the market matrix, is a schedule which specifies which salesman calls on each customer, and the sales call frequencies which maximize the total sales from all territories. A case example illustrates how the procedure is applied.